2022
DOI: 10.1002/cphc.202200558
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Potential of Multinuclear Solid‐State 1H, 13C, and 35Cl Magnetic Resonance To Characterize Static and Dynamic Disorder in Pharmaceutical Hydrochlorides

Abstract: Crystallographic disorder, whether static or dynamic, can be detrimental to the physical and chemical stability, ease of crystallization and dissolution rate of an active pharmaceutical ingredient. Disorder can result in a loss of manufacturing control leading to batch-to-batch variability and can lengthen the process of structural characterization. The range of NMR active nuclei makes solid-state NMR a unique technique for gaining nucleus-specific information about crystallographic disorder. Here, we explore … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 93 publications
0
6
0
Order By: Relevance
“…28–31 The rare exploitation of the 35 Cl resonance is probably due to the fact that for halide ions spin relaxation times can become fairly short (down to the μs regime). 32,33 Nevertheless, the 35 Cl probe was utilized 34 to explore static material properties for ordered crystals, 35–37 glassy crystals, 38 and glasses, 39 and for liquids as well. 40–42…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…28–31 The rare exploitation of the 35 Cl resonance is probably due to the fact that for halide ions spin relaxation times can become fairly short (down to the μs regime). 32,33 Nevertheless, the 35 Cl probe was utilized 34 to explore static material properties for ordered crystals, 35–37 glassy crystals, 38 and glasses, 39 and for liquids as well. 40–42…”
Section: Introductionmentioning
confidence: 99%
“…To study the mobilities of these components 1 H, 19-23 2 H, 24 13 C 25 and other nuclides 26 were exploited as probes. Even the 35 Cl nuclide (which is three times more abundant than 37 Cl) was already used, however, barely to unravel dynamical properties of DESs, 27 but mostly to monitor hydration-induced chemical shifts. [28][29][30][31] The rare exploitation of the 35 Cl resonance is probably due to the fact that for halide ions spin relaxation times can become fairly short (down to the ms regime).…”
Section: Introductionmentioning
confidence: 99%
“…, the uptake of atmospheric water or the disproportionation of ions due to interactions with excipients), 56,57 quantify the wt% API in dosage forms, 46,56 and even characterize static and/or dynamic disorder in solids. 58 Various 2D SSNMR techniques that exploit (ultra)fast MAS and indirect detection of low-γ nuclides have been developed in recent years, 59–63 which could enhance understanding of H⋯Cl − hydrogen bonding arrangements and their complex relationships with 35 Cl EFG tensors. Finally, the advent of ultra-high field NMR ( e.g.…”
Section: Introductionmentioning
confidence: 99%
“…44-50 35 Cl SSNMR methods also have the ability to identify chemical changes that occur within dosage forms (e.g., the uptake of atmospheric water or the disproportionation of ions due to interactions with excipients), 56,57 quantify the wt% API in dosage forms, 46,56 and even characterize static and/or dynamic disorder in solids. 58 Various 2D SSNMR techniques that exploit (ultra)fast MAS and indirect detection of low-γ nuclides have been developed in recent years, [59][60][61][62][63] which could enhance understanding of H⋯Cl − hydrogen bonding arrangements and their complex relationships with 35 Cl EFG tensors. Finally, the advent of ultra-high field NMR (e.g., using fields up to 35.2 T), possibly augmented through use of MQMAS techniques, [64][65][66] is expected to advance applications of 35 Cl SSNMR spectroscopy for the study of complex API solid forms with multiple overlapping patterns, including heterogeneous mixtures and amorphous solid dispersions.…”
Section: Introductionmentioning
confidence: 99%
“…Our group and others have demonstrated that 35 Cl SSNMR spectroscopy is invaluable for rapid fingerprinting and differentiation of different solid forms of the APIs in both bulk and dosage forms, as well as probing the local geometries of ions, including the types, numbers, and arrangements of chemical species participating in H···Cl – hydrogen bonding. The 35 Cl SSNMR spectra of chloride ions in organic HCl salts almost always feature broad central-transition (CT, +1/2 ↔ −1/2) powder patterns that are influenced by the second-order quadrupolar interaction (SOQI), and in many cases, chlorine chemical shift anisotropy (CSA). The 35 Cl electric field gradient (EFG) tensor, which gives rise to the QI, is extremely sensitive to changes and/or differences in chloride ion environments that result from distinct hydrogen-bonding arrangements.…”
Section: Introductionmentioning
confidence: 99%